PANDANGAN GENERASI Z TERHADAP PENGGUNAAN DOPING DEMI PRESTASI OLAHRAGA - Nimrot Manalu; Ariel Ginting; Della Wiyanti; Sasta Syehan Yadaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine Generation Z's views on the use of doping in sports to achieve achievement. The study used a quantitative approach with a descriptive survey design. The sample consisted of 120 Generation Z individuals aged 17–25 years old selected through purposive sampling techniques from universities and high schools in Medan City. The instrument used was a Likert-scale questionnaire that had been validated by experts and tested for reliability using the Cronbach's Alpha method. Data analysis was conducted using descriptive statistics and the chi-square test. The results showed that 82% of Generation Z respondents viewed doping as a form of cheating and a violation of sportsmanship values. However, 61% also acknowledged that high competitive pressure was the main motivating factor for athletes to use doping. Furthermore, 74% of respondents considered anti-doping education in schools and on social media to be inadequate. It was concluded that Generation Z has a tendency to have a negative view of doping use.